GA3 and NPK Fertilization Applications Affect Phalaenopsis amabilis L. orchid for Plant Growth - Sunawan, Sunawan; Handoko, Rose Novita Sari; Rahayu, Istiqomah Rusdiana; Afandhi, Aminudin (Graduate Program, 2020)
Application of GA3 and NPK fertilizers is already known to promote growth of plants. Potential effects of GA3 and NPK on the growth of Phalaenopsis ambilis L. orchid were investigated in the present study. However, increasing application GA3 concentrations of 0, 1, 2, 3, 4, 5 ppm/plant and NPK concentrations of 0, 1, 2, 3, 4 gram/plant. The observation started 30, 45, 60, 75, 90 days after application. This research was use the concentration of GA3 and NPK separately (without combination), each treatment showed a significant effect on the number of leaves, stem diameter, leaf area and leaf area index and had no significant effect to plant height variables. Treatment of GA3 (3 ppm / plant) showed positive results on the variable number of leaves, leaf area and leaf area index. Increasing the concentration of GA3 to 5 ppm / plant did not show any significant difference with the treatment of GA3 concentration of 3 ppm / plant. This shows that plants are needed in small amounts. The dose of fertilizer 1 g / plant showed positive results on the variable number of leaves and stem diameter, while for the leaf area variable and leaf area index required higher NPK fertilizer osis ie 2 g / plant. The increase of NPK fertilizer dosage up to 4 g / plant was not significantly different from treatment 1 and 2 g / plant.Keywords: Phalaenopsis ambilis L., GA3, NPK, Growth